Edukasi Pendidikan Kesehatan Dengan Media Elektronik Terhadap Tingkat Kecemasan Remaja Dalam Menghadapi Menarche Di SDN Bengkong - Nuari Andolina; Rici Gusti Maulani; Feny Puput Indrawati (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
One of the factors that influences teenage anxiety is perception teenagers in responding to puberty where young women are more likely to give negative response to the puberty process they are experiencing. Currently, many midwives provide education about puberty, but unfortunately few midwives do provide education about puberty using related electronic media how to deal with menarche. The purpose of this community service is to find out the effectiveness of electronic media on adolescent anxiety in facing menarche at SD N. This research is a quasi-experiment with a pretest and posttest design control group design and the population in this study were 40 premenarche students with aged 9-12 years with a sample of 20 students as a control group and 20 students as the experimental group. Data collection is obtained by filling in HARS anxiety level questionnaire and the analysis used was the Wilcoxon test and Mann Whitney. The results of this research show that there is an influence electronic media education on adolescent anxiety in facing menarche in SD N with a p value of 0.004 < 0.05.